The Effect of Single-Leg and Double-Leg Hurdle Jumps on Shooting Speed (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aimed to compare the effectiveness of double-leg hurdle jumps and single-leg hurdle jump training in increasing the shooting speed of football players at SMPN 3 Bontomarannu. This research method uses an experimental design with a paired sample t-test to analyze the differences in the results of the two training methods. The research sample consisted of 22 players divided into two groups, each doing double leg hurdle jumps training as many as 11 players and single leg hurdle jumps also 11 players for 16 meetings. The results of the study showed that double leg hurdle jumps training produced a mean value of 0.04818 with a significance of 0.000 (p